Expression and prognostic value of MAGE-A9 in laryngeal squamous cell carcinoma - Han, Liang (Int J Clin Exp Pathol, 2014)
Background: Melanoma-associated antigen (MAGE) family genes are reported to play important roles in the development of human cancers. However, the relationship between the expression of MAGE-A9 and clinicopathological characteristics in human laryngeal carcinoma remains unclear. This study aimed to examine the expression of MAGE-A9, and to evaluate the clinical significance of its expression in human laryngeal squamous cell carcinoma (LSCC). Methods: Quantitative real-time reverse transcription-PCR (qPCR) and immunohistochemistry (IHC) were performed to characterize the expression of MAGE-A9 in LSCC tissues and tumor-adjacent normal tissues. Kaplan-Meier survival and Cox regression analyses were performed to evaluate the prognosis of patients with LSCC. Results: The expression of MAGE-A9 was significantly higher in LSCC than in tumor-adjacent normal tissues. Cytoplasmic expression of MAGE-A9 was detected in 70 of 123 (56.9%) LSCC specimens. Levels of MAGE-A9 in LSCC were related to histopathological grade (P = 0.024). Kaplan-Meier survival and Cox regression analysis revealed that MAGE-A9 expression level and lymph node metastasis were independent prognostic factors of LSCC (P = 0.005; P = 0.001, respectively). Conclusions: Our study suggests that MAGE-A9 expression is a prognostic biomarker for LSCC patients. High expression of MAGE-A9 indicates unfavorable survival outcome in LSCC patients.